The Quality of E-Student Worksheet on the Concept of Vertebrate Based on Critical Thinking Skill in Senior High School Level - Erina; Zaini, Muhammad; Kapsul, Kapsul (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2023)
This study aims to describe the quality of E-student worksheet on the concept of vertebrate based on critical thinking in senior hight school. The development research used the Tessmer formative evaluation design, namely: 1) self evaluation; 2) expert reviews; 3) one-to-one evaluation; 4) small group evaluation; and 5) field test evaluation, but in this study only up to small group evaluation. The validity test subjects were three experts, the individual test subjects were three students of class X Senior High School and the small group test subjects were four students in the same class. Expectancy practicality data is obtained from student responses using the expectation practicality assessment sheet instrument. Expected effectiveness data is obtained from the results of the assessment of students' critical thinking skills through the E-student worksheet. The effectiveness of expectations based on the assessment of critical thinking skills in the interpretation aspect obtained a good category, while other aspects including analysis, inference, explanation and self-regulation obtained a very good category. Thus, the quality E-student worksheet on the concept of vertebrate based on critical thinking in senior hight school has a very good category.